Efficacy of Naringenin against aging and degeneration of nucleus pulposus cells through IGFBP3 inhibition - Xiaokai Tang; Junlong Zhong; Hao Luo; Faxin Zhou; Lixia Wang; Sijian Lin; Jiachao Xiong; Hao Lv; Zhenhai Zhou; Honggui Yu; Kai Cao (Scientific Reports)
Abstract Naringenin (NAR), a natural flavonoid, exerts anti-inflammatory and antioxidant pharmacology. However, the pharmacological mechanisms through which NAR prevents and treats intervertebral disc degeneration (IDD) remain unclear. We utilized bioinformatics, machine learning, and network pharmacology to identify shared targets among NAR, senescence, and IDD. Subsequently, molecular docking was conducted to evaluate NAR’s binding affinity to common target. Additionally, we used IL-1β to induce senescence and degeneration in nucleus pulposus cells (NPCs) and conducted a series of cellular assays, including immunoblotting, immunofluorescence, β-galactosidase staining, cell proliferation, cell cycle analysis, and measurement of reactive oxygen species levels, to investigate NAR’s impact on IL-1β-induced senescence and degeneration of NPCs. Our study revealed that Insulin-like growth factor binding protein 3 (IGFBP3) was the only common target. IGFBP3 exhibited significant differences between the IDD and healthy groups and proved to be an effective diagnostic marker for IDD. Molecular docking confirmed the binding between NAR and IGFBP3. In vitro experiments, we observed that Igfbp3 expression increased in the senescence and degeneration groups. Igfbp3 knockdown and NAR attenuated IL-1β-induced senescence and degenerative phenotypes in NPCs. In contrast, the effect of NAR was attenuated by recombinant IGFBP3 protein. In conclusion, our findings suggest that NAR plays a preventive and therapeutic role in IDD, likely achieved through the inhibition of Igfbp3 expression.